2015
DOI: 10.1186/s12871-015-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-methyl-D-aspartate receptor encephalitis associated with an ovarian teratoma: two cases report and anesthesia considerations

Abstract: BackgroundAnti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an immune-mediated syndrome caused by the production of anti-NMDAR receptor antibodies. The syndrome characterised by psychosis, seizures, sleep disorders, hallucinations and short-term memory loss. Ovarian teratoma is the confirmed tumour associated with anti-NMDAR antibodies. The patients with anti-NMDAR encephalitis complicated by ovarian teratoma require surgical treatment under general anesthesia. NMDARs are important targets of many ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A review of 349 PSH case reports found that about 80% of PSH followed TBI, 10% followed anoxic brain injury, 5% followed stroke, and the remaining 5% occurred in association with hydrocephalus, tumors, hypoglycemia, infections, or unspecified causes [7]. To date there were only few case reports available describing the association of anti-NMDAR encephalitis with PSH [8,9]. Of note, although the cases formally diagnosed PSH was rare in anti-NMDAR encephalitis, autonomic instability has been reported in anti-NMDAR encephalitis with a frequency of 69-89% in various case series [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 349 PSH case reports found that about 80% of PSH followed TBI, 10% followed anoxic brain injury, 5% followed stroke, and the remaining 5% occurred in association with hydrocephalus, tumors, hypoglycemia, infections, or unspecified causes [7]. To date there were only few case reports available describing the association of anti-NMDAR encephalitis with PSH [8,9]. Of note, although the cases formally diagnosed PSH was rare in anti-NMDAR encephalitis, autonomic instability has been reported in anti-NMDAR encephalitis with a frequency of 69-89% in various case series [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…NMDARs are heteromers of NMDAR1 and NMDAR2 subunits, which bind with glycine and glutamate, respectively (Tachibana et al, 2013). NMDAR hyperfunction is proposed to result in psychosis (Liu et al, 2015). Anti-NMDAR encephalitis represents a state of NMDAR hypofunction caused by autoantibodies against NMDAR (Warikoo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Total intravenous anaesthesia appears to be an alternative method for maintenance of anaesthesia in patients with SPS and anti-NMDAR encephalitis 26. Propofol, remifentanil and sufentanil infusions have been used to maintain anaesthesia in patients with anti-NMDAR encephalitis without significant adverse effects 27…”
Section: Discussionmentioning
confidence: 99%